Can Hong Kong price-manage its public transportation's ridership?. Issue 4 (December 2020) - Woo, C.K.; Liu, Y.; Cao, K.H.; Zarnikau, J.
Highlights: Analyze Hong Kong public transportation's six mode-specific passenger volumes. Use a 12-year sample of monthly data to document mode-specific price elasticities. Assess price-management of Hong Kong public transportation's ridership. Recommend policies to mitigate Hong Kong's road congestion and vehicular emissions. Abstract: This paper is motivated by the usefulness of own- and cross-price elasticity estimates in managing Hong Kong's demand for public transportation. It uses a 12-year sample of monthly data from January 2006 to December 2017 to estimate a Generalized Leontief system of six mode-specific passenger volume regressions. Its key findings are: (1) the own-price elasticity estimates are −0.45 for taxi, −0.30 for minibus, −0.24 for bus, −0.23 for ferry, −0.06 for tram, and −0.07 for train (i.e., Mass Transit Railway); (2) the cross-price elasticity estimates are positive and smaller in size than the own-price elasticity estimates; and (3) the aggregate own-price elasticity estimate is −0.048 for the entire public transportation system. These findings of low price responsiveness imply that reducing public transportation fares and raising private transportation's average usage cost will likely have a minimal impact on Hong Kong public transportation's ridership. Hence, mitigating Hong Kong's traffic congestion and vehicular emissions may require such policy measures as restricting private car ownership and improving Hong Kong public transportation's non-fare attributes of accessibility and travel time performance.